Pengaruh Knowledge Management, Professionalisme, Dan Talent Management Terhadap Pengembangan Karir (Studi Kasus Pada PT PLN (Persero) UP3 MALANG) - Azez, Muchamad Abdul; Wahono, Budi; Rizal, Mohammad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study is titled ‘The Influence of Knowledge Management, Professionalism, and Talent Management on Career Development (A Case Study at PT PLN (Persero) UP3 Malang)’. The purpose of this study is to determine whether Knowledge Management, Professionalism, and Talent Management influence Career Development in that region. And how they influence it, both partially and simultaneously. This study employs an explanatory research design using quantitative methods. The research was conducted using a questionnaire administered to a sample of 64 employees from a total population of 177 active employees at PT PLN (Persero) UP3 Malang. Data analysis was performed using Multiple Linear Regression analysis with the Statistical Package for the Social Sciences (SPSS) application. The results of the study indicate that Knowledge Management, Professionalism, and Talent Management significantly influence Career Development collectively. Additionally, Knowledge Management and Professionalism do not significantly influence Career Development individually. However, Talent Management significantly influences Career Development individually.  Keywords : Knowledge Management, Professionalism, Talent Management, and Career Development